Kinesiotaping Versus Pilate Exercises on Primary Dysmenorrhea in Girls - Abdelaziz, Amira H.; El-Kosery, Soheir M.; EL-Refaye, Ghada E; Mohamed, Mohamed F. (International Journal of Psychosocial Rehabilitation, 2020)
Back ground: Primary dysmenorrhea (PD) is recurrent, cyclic, crampy pain in girls and its major symptoms were including lower abdominal pain, nausea, vomiting and headache. Therefore, there was a negatively effect on the activities of daily living and the school performance. Purpose: This study was designed to assess the effect of kinesiotaping versus pilate exercises on primary dysmenorrhea in girls. Subjects and Methods: Sixty girls participated in this study and their main complaints were pain and cramping during menstruation.The girls were divided randomly into two equivalent groups. Group (A) :Thirty girls were treated by kinesiotaping during menstruation for 3 consecutive menstruation. Group (B): Thirty girls were treated by pilate exercises, 3 sessions for each week for 3 months with the exception of the days of menstruation. Visual analogue scale to assess pain intensity, Quality of life enjoyment and satisfaction questionnaire, Menstrual Distress Questionnaire, WALIDD score, Spielberger questionnaire and blood test analysis to evaluate plasma prostaglandin level were applied for each girl in two groups before and after the treatment. Results: The obtained results showed a statistically highly significant improvement concerning visual analogue scale, Quality of life enjoyment and satisfaction, Menstrual Distress Questionnaire, Spielberger questionnaire in both groups but the improvement was highly significant improved in group (B) when compared with group (A).There was significant reduction of WALIDD score at post treatment in compare to pre-treatment in both groups but there was no statistical significant difference between both groups. Also, there was significant reduction of prostaglandin at post treatment in compare to pre-treatment in both groups and this significant reduction in favor to group (B) when compared with group (A). Conclusion: The use of pilate exercises appeared to be more effective than kinesiotaping on primary dysmenorrhea in girls.